¿Se necesita la prueba t de Student para dos muestras independientes asumiendo varianzas iguales? (2011)
In this paper we review the behavior of the type I error rate of Student’s t-test and Welch-Sattetthwaite test for comparing two means with independent samples from normal populations under the assumption of homogeneity of variances and under conditions of heteroscedasticity. The results, obtained by the Monte Carlo method show the Welch-Satterthwaite well behaved in all cases.